Ball Beam: projeto, construção e controle de um protótipo de bancada didática - REAL, Rogério Fonseca Côrte (2021)
The present work aims at the development of a didactic bench prototype for a ball beam system, its mathematical modeling and the implementation of a digital controller. The challenge had been launched in the first year of the Electrical Engineering course, by Professor Raphael Teixeira, who developed activities in the Control Laboratory with students from all periods, from freshmen to seniors. The prototype project was developed after research in which several existing ball beam models were evaluated, in addition to suppliers for the materials needed for their manufacture. The components used, actuator and transducers, were the object of extensive studies and tests, determining several characteristics, at first hidden, which impacted the implementation of the controller. The controller project started with mathematical modeling, followed by the definition of performance specifications. A PD control architecture was adopted without the error derivative, but due to the limitations imposed by the actuator and transducers, resources such as compensators, filtering with statistical processing, recursive estimator and predictor were used. The constructive and operational results were close to the theoretical results, so that the resources used to mitigate the limitations of the components used proved to be satisfactory.